The Effect of Publication Media and Negative E-Wom On Employees Work Motivation UD. Sumber Indah Livestock Company in Pandemic Covid-19 - Nasir, Naufal Firhan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study attempts to analyze the effect of publication media and negative e-wom on employees work motivation UD. Sumber Indah livestock company in the covid-19 pandemic. The study is publication media (X1), negative e-wom (X2), and motivation (Y). Publication media has six basic principles based on content of the news in the publicity. Hence, these sixth principle can be measuring instrument or the successful publication by the media, consisting, creativity, quantity, visibility, understandable legality. In that second independent variable is a negative e-wom, which has 3 indicators including intensity, a valence of opinions, and content. While in the dependent variable (Y) Work motivation, which has 3 indicators including the direction to behavior, persistence, and level of effort. The analytical tool used multiple linear regression analysis. The population in this study were all employees of UD Sumber Indah, totaling 97 respondents, so the sampling technique in this study was a saturated sampling technique. The results showed that the media publication variables and negative e-WoM had a significant and partial effect on work motivation of the employees of the UD Sumber Indah livestock company with a significance value of 0.000 each.